131 Human Medial Temporal Lobe Stimulation Between Encoding and Retrieval Selectively Enhances Forgetting. (August 2015) - Merkow, Maxwell B.; Burke, John; Ramayya, Ashwin G.; Sharan, Ashwini D.; Kahana, Michael J.; Sperling, Michael
Abstract : INTRODUCTION: Direct brain stimulation is thought to produce a temporary lesion effect to the surrounding tissue and the synaptically connected network. In the medial temporal lobe (MTL), application of electrical current has been shown to produce memory impairments, but the nature of this effect is unknown. METHODS: To better understand the neurocognitive mechanisms underlying the effect of MTL stimulation on memory, we conducted a free-recall experiment with 5 patients undergoing invasive electroencephalographic monitoring. RESULTS: At 8 bipolar electrode sites, average current density ranged from 9.0 to 39.8 μC/cm 2 per phase. Left MTL stimulation led to worse recall than sham trials (76% vs 83%, P = .003). Crucially, we found that stimulation during the interval between encoding and retrieval led to worse performance than stimulation during the learning or recall periods. (vs encoding P = .047; vs retrieval P = .016). Echoing this finding, response times tended to be slower during this same period (vs retrieval P = .026). We show that our results are not a manifestation of global cognitive impairment, because arithmetic distractor performance was no different between sham and delay-period stimulation trials (94.1% correct vs 93.9% correct, P = n.s.; response times: 4.61 seconds vs 4.70 seconds, P = n.s.) Further, delay-period stimulation diminished a strong primacy effect: subjects were less likely to begin recall with the first item of a list (73.4% vs 81.3%, P = .039). CONCLUSION: We interpret our findings as support for a rapid contextual change account of stimulation-induced forgetting. Stimulation of the MTL may have disrupted neural activity representing temporal context, and thus impaired the internally generated memory search. Alternatively, an interruption of list item maintenance may explain impaired performance. By continuing to refine the cognitive understanding of forgetting-induced MTL stimulation, future research may lead to selective pruning of unwanted memories.